People's Republic of Bangladesh - Revenue Mobilization Program for Results : VAT Improvement Program - World Bank (Washington, DC, 2014)
In accordance with the Bank s OP/BP 9.0 an Integrated Fiduciary Systems Assessment (IFSA) was carried out to determine whether the fiduciary systems pertaining to the Program provide reasonable assurances that the Program funds will be used for their intended purpose. The IFSA comprised an assessment of the fiduciary risks relating to: (a) procurement; (b) financial management; and (c) governance (including fraud and corruption risks) of the implementing agency (the VAT Wing of NBR) which accounts for 95 percent of the Bank-supported Program financing over the next five years. An additional 5 percent of funds will be spent through the ERD as the coordinating agency and the agency responsible for hiring the third party entity for independent verification and reporting to the World Bank. For disbursement purposes, the Bank retains the right to make the final decision whether DLIs have been achieved or not. The conclusion of the IFSA is that the overall fiduciary framework is high risk, but with risk mitigating measures, it is adequate to support Program implementation and to achieve the desired results.